2020
DOI: 10.3390/mi11010087
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate Coatings for Titanium Surfaces to Optimize Biocompatibility

Abstract: Currently, there are more than 1.5 million knee and hip replacement procedures carried out in the United States. Implants have a 10–15-year lifespan with up to 30% of revision surgeries showing complications with osteomyelitis. Titanium and titanium alloys are the favored implant materials because they are lightweight and have high mechanical strength. However, this increased strength can be associated with decreased bone density around the implant, leading to implant loosening and failure. To avoid this, curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The coatings were suggested to be suitable for different biomedical applications. Biomaterial modelling for optimized methacrylate coating for Ti implant biocompatibility was proposed by Sun et al [54]. They applied cheminformatics methods to methacrylated proteins to estimate their suitability as Ti implants coatings.…”
Section: Polymethyl Methacrylate (Pmma)mentioning
confidence: 99%
“…The coatings were suggested to be suitable for different biomedical applications. Biomaterial modelling for optimized methacrylate coating for Ti implant biocompatibility was proposed by Sun et al [54]. They applied cheminformatics methods to methacrylated proteins to estimate their suitability as Ti implants coatings.…”
Section: Polymethyl Methacrylate (Pmma)mentioning
confidence: 99%
“…392 The fibrous tissue capsule, combined with the foreign body giant cell formation, creates a barrier surrounding the implant, leading to limited access to interstitial fluid and impaired function of the sensor. 393,394 To address this, different strategies have been investigated (Figure 10), including surface modification (implant coatings, 395,396 that may have micro-and nanopatterning, 396 with or without surface functionalization) 397,398 and use of fibrotic reaction inhibitory molecules (biomolecules 399 or drugs). 400,401 It was also thought that implant coating can provide the necessary physical, biochemical, structural, and mechanical buffer zone, 402−404 which may help to address challenges facing sensor-integrating implants.…”
Section: Challengesmentioning
confidence: 99%
“…Following implantation, inflammatory cells (macrophages) generate and release various pro-fibrotic factors, leading to the formation of a fibrous capsule around implants and sensors . The fibrous tissue capsule, combined with the foreign body giant cell formation, creates a barrier surrounding the implant, leading to limited access to interstitial fluid and impaired function of the sensor. , To address this, different strategies have been investigated (Figure ), including surface modification (implant coatings, , that may have micro- and nanopatterning, with or without surface functionalization) , and use of fibrotic reaction inhibitory molecules (biomolecules or drugs). , It was also thought that implant coating can provide the necessary physical, biochemical, structural, and mechanical buffer zone, which may help to address challenges facing sensor-integrating implants. For example, it was shown that electrospun membranes with optimized fiber diameter, pore size, and permeability could play a critical role in achieving long in vivo sensing lifetime of implantable glucose biosensors .…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%